Trends in the Diels–Alder reaction in polymer chemistry. (17th August 2021) - Briou, Benoit; Améduri, Bruno; Boutevin, Bernard
Abstract : The Diels–Alder (DA) reaction is regarded as quite a useful strategy in organic and macromolecular syntheses. Abstract : The Diels–Alder (DA) reaction is regarded as quite a useful strategy in organic and macromolecular syntheses. The reversibility of this reaction and the advent of self-repair technology, as well as other applications in controlled macromolecular architectures and crosslinking, have strongly boosted the research activity, which is still attracting a huge interest in both academic and industrial research. The DA reaction is a simple and scalable toolbox. Though it is well-established that furan/maleimide is the most studied diene/dienophile couple, this perspective article reports strategies using other reversible systems with deeper features on other types of diene/dienophile pairs being either petro-sourced (cyclopentadiene, anthracene) or bio-sourced (muconic and sorbic acids, myrcene and farnesene derivatives, eugenol, cardanol). This review is composed of four sections. The first one briefly recalls the background on the DA reactions involving cyclodimerizations, dienes, and dienophiles, parameters affecting the reaction, while the second part deals with the furan/maleimide reaction. The third one deals with petro-sourced and bio-sourced (or products becoming bio-sourced) reactants involved in DA reactions are also listed and discussed. Finally, the authors' opinion is given on the potential future of the crosslinking–decrosslinking reaction, especially regarding the process ( e.g., key temperatures of decrosslinking) or possibly monocomponents. It presents both fundamental and applied research on the DA reaction and its applications.